APPLICATION OF COMPREHENSIVE BUDGET PREPARATION ON UMKM BATIK MALANG (STUDY AT UMKM BATIK BLIMBING - MALANG) - Ulliyawatik, Ulliyawatik (Department of Management, 2017)
This research was conducted for budgeting the comprehensive (Projected Sales Budget Sales, Production Budget, Budget Purchase of Raw Materials, Budget Direct Labor, Budget Overhead, Budget Marketing Costs, Budget and Administration General Budget of Income, Cash Budget, and Balance Sheet) at UMKM Batik Belimbing. Type of research is supporting a research case study using data analysis techniques comprehensive budget forecasting calculations. The method used by the comprehensive budget calculations. The purpose of this research to create a comprehensive budgeting UMKM Batik Blimbing 2016 and 2017.